A Comprehensive Review on Planar Magnetics and the Structures to Reduce the Parasitic Elements and Improve Efficiency - Pouya Kolahian; Ferdinand Grimm; Mehdi Baghdadi (Energies, 2023)
Due to the need for highly efficient and compact power electronic converters to operate at higher frequencies, traditional wire-wound magnetics are not suitable. This paper provides a comprehensive review of planar magnetic technologies, discussing their advantages as well as associated disadvantages. An extensive review of the research literature is presented with the aim of suggesting models for planar magnetics. Several strategies are proposed to overcome the limitations of planar magnetics, including winding conduction loss, leakage inductance, and winding capacitance. The goal of this study is to provide engineers and researchers with a clear roadmap for designing planar magnetic devices.